Cultural Approaches to Disgust and the Visceral - Ryynänen, Max; Kosonen, Heidi S.; Ylönen, Susanne C. (Routledge Advances in Art and Visual Studies, 2023)
This edited volume traces cultural appearances of disgust and investigates the varied forms and functions disgust takes and is given in both established and vernacular cultural practices. Contributors focus on the socio-cultural creation, consumption, reception, and experience of disgust, a visceral emotion whose cultural situatedness and circulation has historically been overlooked in academic scholarship. Chapters challenge and supplement the biological understanding of disgust as a danger reaction and as a base emotion evoked by the lower senses, touch, taste and smell, through a wealth of original case studies in which disgust is analyzed in its aesthetic qualities, and in its cultural and artistic appearances and uses, featuring visual and aural media. Because it is interdisciplinary, the book will be of interest to scholars in a wide range of fields, including visual studies, philosophy, aesthetics, sociology, history, literature, and musicology.